Guava flavonoid glycosides prevent influenza A virus infection via rescue of P53 activity. Issue 1 (24th September 2018) - Khalil, Hany; Abd El Maksoud, Ahmed I.; Roshdey, Tamer; El‐Masry, Samir
Abstract : Influenza is a highly infectious disease caused by three types of viruses, including influenza A virus (IAV), influenza B virus, and, rarely, influenza C virus. IAV is a major, global public health threat, causing approximately 500 000 deaths per year worldwide. The new strains of IAV have emerged due to a mutation called antigenic shift, which results in a new subtype of the virus that shows resistance to common antiviral drugs. Here, guava and lemon extracts, including green leaves and flowers, were investigated for their activity against IAV replication in human A549 cells. Concomitantly, the cytotoxicity of a potent extract on host‐cell multiplication was assessed. Our results reveal that guava extracts inhibit IAV replication, indicated by viral nucleoprotein expression profile and traditional plaque assay. Interestingly, treatment with guava extract inactivates Akt protein kinase and stimulates the pro‐apoptotic protein P53, at early stages of infection. Furthermore, purified guava flavonoid glycosides (GFGs) show competitive inhibition of IAV‐virus replication via early regulation of IL‐1β and IL‐8 in association with P53 gene expression. The docking analysis of GFGs and the protein structure of upstream targets for the Akt signaling pathway indicates a sufficient interaction and stabilization with Gbr2 protein. These data indicate that treatment with GFGs disturbs IAV replication via activation of P53 and its apoptotic related factors after infection. Collectively, these data show that targeting of essential host kinases that are involved in the replication cycle of IAV and rescue of P53 activity by GFGs could represent a new strategy to eradicate IAV.